The Advancing Roles of Internet of Things (Iot) in Europe's Tourism Industry: Public Relations Strategies Post Covid-19 Pandemic - Muhammed Erbay (Jurnal Spektrum Komunikasi, 2023)
As a novel study topic across many academic and industrial fields, including tourism, the Internet of Things (IoT) has gained considerable footing recently. Modern tourist systems are being reshaped by the Internet of Things (IoT) revolution, which considers technological, economic, and social factors. It's changing the way visitors use and manage their interests from conventional to more tailored platforms. The coronavirus 2, which is causing the current worldwide pandemic, is the worst global public health catastrophe since the influenza pandemic of 1918. This witnessed one of the major troubles in the tourism industry, which made it difficult to operate effectively, as restrictions that were put in place to contain the spread of the virus. The role of Public relations (PR) post Covid-19 pandemic has risen and giving the industry more responsibility in ensuring that her brands and clients stay seen and relevant as the stigma surrounding the virus has made people afraid and unwilling to go back to other fun of life like touring and sightseeing. Hence, most industries continue to utilize various ways that could keep them connected to the customers and technology became one of the vital organs of these developments. The Internet of things continues to advance in terms of its implementations across the tourism industry’s PR. This paper will talk about the advancing roles of the IoT in Europe's tourism industry PR. European nations remain the largest when it comes to technological adoptions. As a result, the paper is likely to furnish changes meant to assist the tourist's bookings, customer engagement, search engine optimization (SEO), amongst many others.